Penyuluhan Pemanfaatan Kertas Bekas Menjadi Produk Kerajinan Tangan pada Yayasan Al-Kahfi - Tania Alda; Gina Cynthia Raphita Hasibuan; Nisaul Fadilah Dalimunthe; Muhammad Thoriq Al Fath; Aravi Zalsa Ramadhan; Mhd. Reza Kurniawan Lubis; Rafif Akhmad Al Fandya; Muhammad Syafiq Hisyam (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2022)
The use of paper is increasing from time to time. If not handled properly it will have an impact on the surrounding environment. One way that can reduce the impact to the environment is to recycle the paper waste into a handicraft product that has economic value. Based on this background, a training for community is needed to educate on how to process used paper into valuable handicraft products. This education must be instilled from an early age, so that children begin to understand that by properly processing waste paper, they can produce something of value that will have an impact on increasing income. This training was carried out at the Al-Kahfi Medan Foundation. The object (target audience) of this community service is the children at the Al-Kahfi Medan Foundation. Children at the Al-Kahfi Medan Foundation do not yet know that used paper can be processed into valuable handicraft products, so a socialisation is needed for them. Children will be given training and trained to be able to process used paper into handicraft products and then be able to market and sell it. After being given this training, it is expected that the mindset of the children at the Al-Kahfi Medan Foundation can change from before, namely waste paper waste, with proper handling can become a valuable handicraft product. The method that will be carried out in this community service is to provide training and also practices and then a trial is carried out so that the children at the Al-Kahfi Medan Foundation can understand the mechanism of processing the used paper into handcraft products.